Chaotic Dynamics in Joint Price QoS Game with Heterogeneous Internet Service Providers - Ait Omar, Driss; Garmani, Hamid; Es-Sabery, Fatima; El Amrani, Mohamed; Azougaghe, Es-Said; Baslam, Mohamed (Journal of Computer Networks and Communications, 2022)
This paper tries to investigate the complex characteristics of the communication market where Internet service providers (ISP) lease network access services and compete to serve a large pool of subscribers. For this purpose, we analyze the dynamics of a mixed duopoly game with two decision parameters: price and quality of service (QoS). We calculate and discuss the stability of each equilibrium solution by using the nonlinear system. A numerical simulation is used to show the flip bifurcation to chaos by the decisions of ISPs with different statuses. We discovered that the Nash equilibrium loses stability when the speed of adjustment and transmission fee increase. We show that the system parameter changes the stability of the communication market. In addition, we use a control method to keep the communication market in a stable state.